A novel proof of Watson’s contour integral representation for r+1φr - Wang, Xiang-Li; Liu, Dong-Fang; Luo, Qiu-Ming (Utilitas Mathematica, 2016)
In this paper we give a simple proof of Watson's contour integral representation for r+1φr by applying Cauchy's operators, and obtain an interesting formula of contour integral representation for (q;q)r∞.